Advanced quality go on bussiness thought management student in military schools before impact belong to the dark side of the market mechanism currently - Nguyễn Quang Bình; Trần Quốc Khánh; Lê Văn Tình (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
The article focuses on clarifying the need to improve the quality of student ideological management in military schools against the impact of the negative side of the market mechanism. Currently, the negative sides of the market mechanism, evils, and negative phenomena in society have significantly affected the awareness, emotions, beliefs, and ideas of students in military schools, impacting directly to the motivations, career trends of learners and the training goals and requirements of each school. Based on an overview of the impacts, the article proposes a number of main measures to improve the quality of student ideological management in military schools against the impact of the negative side of the current market mechanism.